2017
DOI: 10.1103/physrevx.7.041065
|View full text |Cite
|
Sign up to set email alerts
|

External Potential Modifies Friction of Molecular Solutes in Water

Abstract: Stokes's law for the friction of a sphere in water has been argued to work down to molecular scales, provided the effective hydrodynamic radius includes the hydration layer. In interpretations of experiments and in theoretical models, it is tacitly assumed that the solvent friction experienced by a solute does not depend on whether an external confinement potential acts on the solute. Using a novel method to extract the friction memory function from molecular dynamics simulations, we show that the solvent fric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
115
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(138 citation statements)
references
References 60 publications
14
115
0
Order By: Relevance
“…(Let us be reminded that this potential does not act on the bath particles in equation (9), in contrast to the analysis provided in [59]). This dependence has indeed been observed in computer simulations of molecular solutes in water in [47].…”
Section: Hamilton Dynamicssupporting
confidence: 66%
See 2 more Smart Citations
“…(Let us be reminded that this potential does not act on the bath particles in equation (9), in contrast to the analysis provided in [59]). This dependence has indeed been observed in computer simulations of molecular solutes in water in [47].…”
Section: Hamilton Dynamicssupporting
confidence: 66%
“…Combining experimental measurements, analytical computations, and simulations of a stochastic Prandtl-Tomlinson model, we investigated several equilibrium-properties of a colloidal particle suspended in a nonlinear bath. Additionally to displacements being non-Gaussian, a nonlinear bath shows up by unexpected properties of the coefficients of a linearized equation; For example, in a nonlinear bath, the effective friction memory of the bath can depend on the stiffness of a potential trapping the particle, as has been observed in molecular simulations [47], or on the mass or bare friction of the colloidal particle. These dependencies are observed in our experiments, so that the friction memory of the trapped particle varies by more than a factor of two for trap stiffnesses κ ranging from 1.89 μN m −1 ... 7.29 μN m −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the Boltzmann relation F(r) = −k B T In(g(r)), we obtain the potential of mean force F(r) for anion-cation pairs ( Fig. 2c), where k B and T are the Boltzmann constant and temperature, respectively 45 . F(r) thus contains excluded volume effects of both water and ions as well as attractive intermolecular interactions.…”
Section: Resultsmentioning
confidence: 99%
“…It is crucial that we extract without applying constraints along the reaction coordinate , as the pronounced differences in the barrier-crossing dynamics between free and constrained butane show that constraints decisively influence the system dynamics. In fact, recent simulation work demonstrated that friction is modified by positional constraints even for the simple system of a methane molecule that diffuses in water ( 52 ). in Eq.…”
Section: Resultsmentioning
confidence: 99%